Exploring the narratives of Malaysian undergraduate students on service-learning experience in eco-tourism industries - Mohd Zaid, Mohd Fakhrul Azizie; Omar, Mohd Khaizer; Muhamad, Mohd Mokhtar (Ubiquity Press, 2020)
As one of the teaching strategies that promote students with hands-on experiences linked with the community engagement, service-learning (SL) has been uniquely positioned favourable in higher education institutions. Precisely, SL is closely related to work integrated learning (WIL) in regards to blending theories with practicality. This study was primarily aimed to explore what Malaysian undergraduate students learned based on their experience in SL project. Eco-tourism industries in Malacca are represented as the community partners that also involved in the project. Twenty informants were selected among 80 students and interviewed through focus group discussions using semi-structured questions. Based on the analysis using constant comparative method, the findings revealed and discussed three emerging themes namely self-value, knowledge-sharing and managing conflicts. The application of SL components involving real situations with the community partners had stimulated broad experience in terms of students’ knowledge and values development.